Fresh leaves of ora-pro-nóbis in cakes prepared from commercial pre-mixture (Bioscience Journal, 2020)
Establishing good infant eating habits in childhood is quite important for proper growth and development. The increasing number of mothers who work outside home has made children have their meals in day care centers or schools. In addition, meals have their preparation being replaced by more suitable options, like instant food, lately depriving kids from good eating and nutritional habits. Such kind of food does not contribute to the formation of good eating habits. Thus, vegetables such as the ora-pro-nóbis (unconventional vegetable, known in English language countries as Barbados Goosenberry and cientific name Pereskia aculeata Miller) that have in their leaves proteins, fibers and minerals, like iron, can contribute to improve the childlike feeding. In order to improve the nutritional value of commercial chocolate cake premixes, in natura ora-pro-nóbis leaves were added in at ratios of 0 (standard), 10, 20, 30 and 40% leaf weight per dough weight, which were covered with chocolate kind icing. Moisture, ashes, lipids, proteins, crude fiber and carbohydrate and total caloric content (VCT) were analyzed in the elaborated formulations. The results showed a significant increase in water retention, crude fiber content and decrease in total caloric value (VCT) in the added cakes of ora-pro-nóbis leaves.